Epidermal Barrier Integrity is Associated with Both Skin Microbiome Diversity and Composition in Patients with Acne Vulgaris - Zhou L; Liu X; Li X; He X; Xiong X; Lai J (Dove Medical Press, 2022)
Lin Zhou,1 Xueping Liu,1 Xulin Li,1 Xiangyan He,1 Xia Xiong,1,* Jingdong Lai2,* 1Department of Dermatology & STD, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 2Department of Dermatology & STD, Suining First People's Hospital, Suining, People's Republic of China*These authors contributed equally to this workCorrespondence: Jingdong Lai; Xia Xiong, Tel +86-13679670608 ; +86-13608282035, Fax +86-08303165651 ; +86-08303165232, Email 987047361@qq.com; xiongxia789@126.comBackground: Although the changed lipid environment of the pilosebaceous unit and the growth of lipophilic Cutibacterium acnes (C. acnes) during puberty has long been considered as the trigger of acne vulgaris, the involvement of the interaction between the epidermal barrier integrity and the skin microbiome in this disease has not been fully elucidated.Objective: The aim of this study was to analyze the differences in the epidermal barrier and skin microbiota in patients with acne vulgaris and their correlation.Methods: The skin microbial samples and epidermal barrier data from 74 acne patients and 19 healthy subjects were collected in this cross-sectional study. The microbial diversity was analyzed based on a high-throughput sequencing approach that targets the V3-V4 region of the bacteria 16S ribosomal RNA genes.Results: Compared with healthy controls, acne patients had significantly increased transepidermal water loss (TEWL), pH levels, sebum, porphyrins, and red areas, and reduced skin microbiome diversity according to the goods coverage diversity index (p = 0.021), Shannon diversity index (p = 0.037), and Simpson diversity index (p = 0.023). Moreover, the diversity gradually decreased with the increase in acne grading. Based on the principal coordinate analysis (PCoA) analysis plot, the skin microbiota of acne patients and healthy controls could be divided into two different sets, which could not be used to separate acne patients with different disease severity. Finally, this study found that both TEWL and sebum were negatively associated with the Shannon and Simpson diversity index. Meanwhile, the taxa Enhydrobacter and Stenotrophomonas were positively associated with TEWL, stratum corneum hydration, respectively.Conclusion: This study demonstrated that acne vulgaris exists in patients with both damaged epithelial barriers and associated microbiota dysbiosis; the findings will help improve the understanding of the disease and may contribute to the development of better treatment options.Keywords: epidermal barrier, skin microbiome